The spatial-temporal dynamics of potato agrobiodiversity in the highlands of central Peru: a case study of smallholder management across farming landscapes - Arce, A.; Haan, Stef de; Juarez, H.; Burra, Dharani Dhar; Plasencia, F.; Ccanto, Raul I.; Polreich, S.; Scurrah, M. (MDPI, 2019)
In the high Andes, environmental and socio-economic drivers are transforming agriculture and presumably affecting the in situ conservation of potato (Solanum spp.). To monitor the use and conservation of intraspecific diversity, systematic and comparative studies across agricultural land-use systems are needed. We investigated the spatial-temporal dynamics of potato in two landscapes of Peru’s central Andes: A highland plateau (Huancavelica) compared to an eastern slope (Pasco). We examined household-level areal allocations, altitudinal distribution, sectoral fallowing practices, and the conservation status for three main cultivar groups: (i) Bred varieties, (ii) floury landraces, and (iii) bitter landraces. Mixed methods were used to survey 323 households and the 1101 potato fields they managed in 2012–2013. We compared the contemporary altitudinal distribution of landraces with 1975–1985 altimeter data from the International Potato Center. Intensification is occurring in each landscape while maintaining high intraspecific diversity. Access to land and production for sale compared to consumption significantly affected smallholder management and differentiated landscapes. Most landraces were scarce across households: 45.4% in Huancavelica and 61.7% in Pasco. Potato cultivation has moved upward by an average of 306 m since 1975. Landrace diversity is versatile but unevenly distributed across landscapes. This requires adaptive ways to incentivize in situ conservation.